Evidence for the Identity of Shared 5′-Terminal Sequences Between Genome RNA and Subgenomic mRNA's of B77 Avian Sarcoma Virus - Stoltzfus, C. Martin (1979)
The polyribosomal fraction from chicken embryo fibroblasts infected with B77 avian sarcoma virus contained 38S, 28S, and 21S virus-specific RNAs in which sequences identical to the 5′-terminal 101 bases of the 38S genome RNA were present. The only polyadenylic acid-containing RNA species with 5′ sequences which was detectable in purified virions had a sedimentation coefficient of 38S. This evidence is consistent with the hypothesis that a leader sequence derived from the 5′ terminus of the RNA is spliced to the bodies of the 28S and 21S mRNA's, both of which have been shown previously to be derived from the 3′ terminal half of the 38S RNA. The entire 101-base 5′ terminal sequence of the genome RNA appeared to be present in the majority of the subgenomic intracellular virus-specific mRNA's, as established by several different methods. First, the extent of hybridization of DNA complementary to the 5′-terminal 101 bases of the genome to polyadenylic acid-containing subgenomic RNA was similar to the extent of its hybridization to 38S RNA from infected cells and from purified virions. Second, the fraction of the total cellular polyadenylic acid-containing RNA with 5′ sequences was similar to the fraction of RNA containing sequences identical to the extreme 3′ terminus of the genome RNA when calculated by the rate of hybridization of the appropriate complementary DNA probes. This suggests that most intracellular virus-specific RNA molecules contain sequences identical to those present in the 5′-terminal 101 bases of the genome. Third, the size of most of the radioactively labeled DNA complementary to the 5′-terminal 101 bases of the genome remained unchanged after the probe was annealed to either intracellular 38S RNA or to various size classes of subgenomic RNA and the hybrids were digested with S1 nuclease and denatured with alkali. However, after this procedure some DNA fragments of lower molecular weight were present. This was not the case when the DNA complementary to the 5′-terminal 101 bases of the genome was annealed to 38S genome RNA. These results suggest that, although the majority of the intracellular RNA contains the entire 101-base 5′-terminal leader sequence, a small population of virus-specific RNAs exist that contain either a shortened 5′ leader sequence or additional splicing in the terminal 101 bases.